5(t-8)/2=t-5

Simple and best practice solution for 5(t-8)/2=t-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(t-8)/2=t-5 equation:



5(t-8)/2=t-5
We move all terms to the left:
5(t-8)/2-(t-5)=0
We get rid of parentheses
5(t-8)/2-t+5=0
We multiply all the terms by the denominator
5(t-8)-t*2+5*2=0
We add all the numbers together, and all the variables
5(t-8)-t*2+10=0
We multiply parentheses
5t-t*2-40+10=0
Wy multiply elements
5t-2t-40+10=0
We add all the numbers together, and all the variables
3t-30=0
We move all terms containing t to the left, all other terms to the right
3t=30
t=30/3
t=10

See similar equations:

| 2.3=-3.2=+x/5 | | X²+6x=1 | | 1.6=b=8 | | 2.3=-3.2=x/5 | | 5x+17=3x+49 | | 9x+8/4+8x-2/3=21 | | 5x^2-8x-40=0 | | 6(n-5)-3n=3 | | 5(x+3)-3x=30 | | 4(n+1)=3(n-1) | | 2x–5=37 | | 2x–5=37. | | 4(x+7)-1=4x+27 | | 0=5+17t-16t^2 | | -4.8f=6.4=-8.48 | | 9(w-7)=-2w+47 | | 2m+3m-1=24 | | -(2-6n)=18+n | | 7-6m-1=24 | | 3x^2+36x+4=0 | | 6(x-1)-2(5x-4)=-10 | | 8(8n-2)=40n+8n | | -1/4(8a+20)=-2a+5 | | 7/8=3x | | 2t-5=-10t | | 7-4(x+1)=9-5x | | 8/3=-4/3+x | | Z=-1-3i | | 4n+1=95 | | 3z/10+6=-2Z= | | 4x÷5=x+26 | | 6x+4=-22 |

Equations solver categories